IMPLEMENTASI PERILAKU HIDUP BERSIH DAN SEHAT DENGAN KEJADIAN DIARE PADA ANAK DI SD AR-RAHMAN MEDAN - Aceh, Arif Rahman; Purba, Jesmo Aldoran; Cerin, Fitria (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
Diarrhea often attacks babies and toddlers, if not treated further, diarrhea will cause dehydration and lead to death. The aim of this research is to implement clean and healthy behavior in the school environment. This research uses a cross-sectional correlative analytical descriptive observational approach. This research was conducted at SD Ar-Rahman Medan with a population of 256 people. The sampling technique was Accidental Sampling of 90 people. This research uses a questionnaire measuring tool with multivariate analysis. The results of the study concluded that there is a relationship between clean and healthy living behavior in terms of influencing the incidence of diarrhea simultaneously (simultaneously) with a significance level of ? = 0.05. The conclusion is that the three categories of clean and healthy living behavior consisting of hand washing, healthy snacks and healthy latrines have the same ability to simultaneously influence the incidence of diarrhea.